Metal–Organic Frameworks‐Based Fabry−Pérot Cavity Encapsulated TiO2 Nanoparticles for Selective Chemical Sensing. (20th November 2021) - Li, Zhihuan; Liu, Jianxi; Yi, Xiaobin; Wu, Wei; Li, Fanfan; Zhu, Zhenkang; Li, Haiqi; Shi, Junqin; Xu, Yadong; Zhou, Feng; Liu, Weimin
Abstract: This paper reports a Fabry−Pérot (F–P) cavity constructed by metal–organic frameworks (MOFs) encapsulated with TiO2 nanoparticles that can achieve selective sensing of chemicals. The MOFs‐based F–P cavity is fabricated by sequentially spray‐coating TiO2 in HKUST‐1 thin films through a layer‐by‐layer deposition strategy. The bandwidth of the cavity is tuned over a broad range by adjusting the thickness and refractive index of the HKUST‐1⊃TiO2 thin films with controllable TiO2 size and concentration. Selective sensing of chemical vapors is demonstrated on the HKUST‐1⊃TiO2 cavities which are attributed to enhanced interaction between hydroxyl groups on the surface of TiO2 and the specific oxygen‐containing analytes. In addition, molecule dynamics simulation and infrared absorption spectrum characterization are conducted to elucidate the mechanism of enhanced sensing properties. Homogeneous encapsulation of functional guest pieces with smaller sizes in MOF films contributes to specific physical–chemical properties that benefit their device applications in optical communication and chemical sensing. Abstract : A metal–organic frameworks‐based Fabry−Pérot (F–P) cavity is constructed by sequentially spray‐coating TiO2 nanoparticles in HKUST‐1 thin films through a layer‐by‐layer deposition strategy. Bandwidth of the cavity is tuned over a broad range by adjusting the thickness and refractive index of their diagram layers. Notably, selective sensing of chemical vapors is achieved on the F–P cavities.